Girl Education: A Way to Empowering Nation (International Journal of Innovative Research in Engineering & Management, 2021)
Education is an important factor for all Regardless of gender, a  kid is a child. However, some communities continue to oppose  females' education. Girls' empowerment, success, growth, and  well-being are all influenced by their education. From the  womb until the tomb, a child's future is fully known. In all  areas, including economics, tutoring, social, political, health  care, nutrition, and rights, as well as legal, there is persistent  disparity and vulnerability of females. A girl's life will be filled  with difficulties if her parents and guardians do not assist her  together in noble way. Education is a means of empowering  people and making life easier for them. Furthermore, prejudice  against a female kid and a masculine child has existed from her  birth. A child's upbringing in the countryside vs the city plays  a vital role in her life duration, since urban culture improves a  little for female children. The most important thing is to  influence people's thinking, since that's the only ability to form  a good difference for a girl. The focus of the current article is  on a girl's condition and the corrective measures done in her life  to prepare the path for her success overall development.
Keywords: Development; Gender; Girls; Growth; Women Education